2020
DOI: 10.1177/1029864920948572
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Chinese Involuntary Musical Imagery Scale and its Application in Mainland China

Abstract: This study aimed to examine the validity and reliability of the Chinese version of the Involuntary Musical Imagery Scale and its application in mainland China. Two studies were conducted. In Study 1, the Involuntary Musical Imagery Scale contents were translated into Chinese and semi-structured interviews were conducted with 10 undergraduate students; on this basis, a preliminary version of the Chinese Involuntary Musical Imagery Scale was generated. Subsequently, the psychometric properties of the Chinese Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Deren interne Konsistenz umfasst Werte von Cronbach's α = ,76 bis ,91, die Test-Retest-Reliabilität erstreckt sich von Cronbach's α = ,65 bis ,79; zudem korrelieren die vier Faktoren mit Mind-Wandering (r von ,12 bis ,28) und kognitiver Intrusion (r von ,07 bis ,22) sowiemusikalischer Erfahrenheit (r von ,12 bis ,34). Die Reliabilitätswerte in der leicht modifizierten chinesischen Version(Jue et al, 2022) sind ähnlich gut (von Cronbach's α = ,66 bis ,90; Test-Retest-Reliabilität von Cronbach's α = ,55 bis ,72). Zudem zeigt der IMIS keine systematische Verzerrung hinsichtlich musikalischer…”
unclassified
“…Deren interne Konsistenz umfasst Werte von Cronbach's α = ,76 bis ,91, die Test-Retest-Reliabilität erstreckt sich von Cronbach's α = ,65 bis ,79; zudem korrelieren die vier Faktoren mit Mind-Wandering (r von ,12 bis ,28) und kognitiver Intrusion (r von ,07 bis ,22) sowiemusikalischer Erfahrenheit (r von ,12 bis ,34). Die Reliabilitätswerte in der leicht modifizierten chinesischen Version(Jue et al, 2022) sind ähnlich gut (von Cronbach's α = ,66 bis ,90; Test-Retest-Reliabilität von Cronbach's α = ,55 bis ,72). Zudem zeigt der IMIS keine systematische Verzerrung hinsichtlich musikalischer…”
unclassified
“…The rotated factor structure for the scale, and the resulting subscale structures, followed exactly the pattern of that reported in Floridou et al’s (2015) Study 2. Unfortunately, comparisons to the factor analytic results of Jue et al’s (2020) study in mainland China were not possible because these authors added and removed items from the original IMIS, and subsequently found a factor solution with two novel dimensions, interpreted as Spare cognitive capacity, and Mind-wandering.…”
Section: Discussionmentioning
confidence: 99%
“…What appears to be generally absent from the INMI literature, including work that utilizes the IMIS, is research in contexts and using samples other than those that are European or American. There are currently three exceptions that we are aware of: a Twitter-based study of earworm-related tweets by Liikkanen et al (2015) that sampled tweets from 173 countries, an experimental study of earworm induction and working memory in a South African student sample (Geffen & Pitman, 2019), and a recent study on the adaptation and validation of the IMIS in mainland China (Jue et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion, adhering to high psychometric standards is not only important for the development of questionnaires but also for their translation into other languages. For example, high psychometric standards were met for the following translations: Gouveia, Pimentel, Lima de Santana, Chaves, and Andrade da Paraı ´ba (2008) published the Portuguese (Brazilian Portuguese) version of the Short Test of Music Preference; Zarza Alzugaray, Herna ´ndez, Lo ´pez, and Gil (2015) validated the Spanish translation of the Kenny Music Performance Anxiety Inventory; Lin, Kopiez, Mu ¨llensiefen, and Wolf (2021) validated the Chinese version of the Gold-MSI for a Taiwanese sample; and Jue, Jianping, and Yiduo (2020) applied the same procedure to the Chinese version of the Involuntary Musical Imagery Scale.…”
mentioning
confidence: 99%